Macroion molecule properties from slender body hydrodynamics. (21st April 2021) - Adamczyk, Zbigniew; Batys, Piotr; Płaziński, Wojciech; Morga, Maria; Lupa, Dawid; Michna, Aneta
Abstract: The all‐atom molecular dynamics simulations were applied to determine physicochemical parameters for poly‐l ‐lysine (a cationic macroion) and λ‐carrageenan (an anionic polysaccharide macroion) comprising the monomer length and the density. The molecule chain diameter for an equivalent cylinder was also calculated. These results were used for the interpretation of experimental data derived from dynamic viscosity measurements of macroion solutions enabling the intrinsic viscosity to be determined. It was confirmed that the molecules assume extended rod‐like conformations in dilute NaCl solutions. Considering the slender body hydrodynamics, the length to diameter parameter (aspect ratio) of the molecules was calculated as a function of their intrinsic viscosity. Using this parameter, the molar mass of macroions can be precisely calculated from a linear dependence derived in this work. The proportionality constant can be ab initio calculated using molecular dynamics modeling. It is confirmed that the formula yields reliable results for both anionic and cationic macroions. Except for the molar mass, the method can be used to predict the diffusion coefficient, the hydrodynamic diameter, the radius of gyration, and the sedimentation coefficients of macroion molecules in dilute electrolytes.